Clinicopathological analysis of 80 cases of oral lobular and non lobular capillary hemangioma (pyogenic granuloma): A Retrospective study - Shareef, Karrar N; Abdullah, Bashar H (Journal of Baghdad College of Dentistry, 2022)
Background: Oral pyogenic granuloma (PG) is a clinicopathological entity that could develop due to the reaction to a variety of stimuli, such as low-grade local irritation, traumatic damage, and hormonal stimulation. There are two histopathological types of pyogenic granuloma; lobular type -capillary hemangioma (LCH) and non-lobular type; with PG,LCH has highly vascular, diffuse capillary growth while non- lobular variant mimicking granulation tissue with heavily inflammated stroma. The study aims were to review the clinical and histopathological spectrum of an oral pyogenic granuloma from different intraoral sites in order to avoid diagnostic pitfalls associated with similar morphological lesions and to determine whether lobular and non-lobular histopathological subtypes being distinct entities. Materials and Methods: A retrospective review of eighty formalin-fixed paraffin-embedded tissue blocks (40 cases each of males and females) were retrieved from the archives of Oral & Maxillofacial Pathology at the University of Baghdad, from 1979 to 2017. According to Mills et al., criteria for lobular capillary hemangioma description, the diagnosis of each case was confirmed by the examination of Hematoxylin and Eosin stained sections by an expert pathologists. Results:The present result revealed that patients with oral pyogenic granuloma were with age range from 12 to 59 years, with a mean of 30.57 years. Fourty nine cases (61.25%) out of eighty were of lobular pattern and 31 cases (38.7%) of non-lobular pattern type PG. The most common site of LCH was in the buccal mucosa, 12 cases (75%), while higher case numbers were observed in the 21-30 year age group. There were non-significant differences between lobular and non-lobular pattern prevalence regarding age groups and between other studied variables. Conclusio: It has been proposed that LCH and non-LCH subtypes reflect distinct phases in the development of a single lesion, which exhibits variable degrees of proliferative, angiogenic, and inflammatory activities.